The influence of pretreatment chemistry on the radiocarbon dating of Campanian Ignimbrite-aged charcoal from Kostenki 14 (Russia) - Douka, K; Higham, T; Sinitsyn, A (Elsevier, 2010)
The presence of an independently dated marker in an archaeological site offers rare opportunties for assessing the reliability of radiocarbon dates, especially when these are close to the age limit of the technique. Two different pretreatment protocols (routine ABA and more rigorous ABOx-SC) were employed in the chemical preparation of the same charcoal sample from a layer closely associated to the Campanian Ignimbrite tephra at the Russian Palaeolithic site of Kostenki 14 (Markina Gora). The ABA-treated fraction gave an age of ~33 14C ka BP, comparable to a previous determination from the same layer, whereas the ABOx-SC produced an older age of ~35 14C ka BP. This is the first radiocarbon determination of an archaeological sample to provide an age consistent with the "calendar" age for the CI tephra marker.